Sprint interval and traditional endurance training increase net intramuscular triglyceride breakdown and expression of perilipin 2 and 5. (18th December 2012) - Shepherd, S. O.; Cocks, M.; Tipton, K. D.; Ranasinghe, A. M.; Barker, T. A.; Burniston, J. G.; Wagenmakers, A. J. M.; Shaw, C. S.
Key points: Increases in aerobic capacity and intramuscular triglyceride (IMTG) utilization are well‐described adaptations to endurance training (ET) and contribute to improvements in insulin sensitivity. Sprint interval training (SIT) also improves aerobic capacity and insulin sensitivity with a lower time commitment than ET. This study aimed to determine whether SIT also induces improvements in insulin sensitivity and net IMTG breakdown, and to investigate the underlying mechanisms. Six weeks of ET and SIT increased net IMTG breakdown during moderate‐intensity cycling, and improved insulin sensitivity. A greater concentration of lipid droplet‐associated proteins, perilipin 2 and perilipin 5, was observed following both training modes and contributes to the increases in net IMTG breakdown following training. The results suggest a novel mechanism for the training‐induced improvements in IMTG breakdown and insulin sensitivity, and clearly demonstrate that SIT is an alternative, time‐efficient training strategy that induces similar beneficial metabolic adaptations. Abstract  Intramuscular triglyceride (IMTG) utilization is enhanced by endurance training (ET) and is linked to improved insulin sensitivity. This study first investigated the hypothesis that ET‐induced increases in net IMTG breakdown and insulin sensitivity are related to increased expression of perilipin 2 (PLIN2) and perilipin 5 (PLIN5). Second, we hypothesized that sprint interval training (SIT) also promotes increases in IMTG utilization and insulin sensitivity. Sixteen sedentary males performed 6 weeks of either SIT (4–6, 30 s Wingate tests per session, 3 days week −1 ) or ET (40–60 min moderate‐intensity cycling, 5 days week −1 ). Training increased resting IMTG content (SIT 1.7‐fold, ET 2.4‐fold; P < 0.05), concomitant with parallel increases in PLIN2 (SIT 2.3‐fold, ET 2.8‐fold; P < 0.01) and PLIN5 expression (SIT 2.2‐fold, ET 3.1‐fold; P < 0.01). Pre‐training, 60 min cycling at ∼65% pre‐training decreased IMTG content in type I fibres (SIT 17 ± 10%, ET 15 ± 12%; P < 0.05). Following training, a significantly greater breakdown of IMTG in type I fibres occurred during exercise (SIT 27 ± 13%, ET 43 ± 6%; P < 0.05), with preferential breakdown of PLIN2‐ and particularly PLIN5‐associated lipid droplets. Training increased the Matsuda insulin sensitivity index (SIT 56 ± 15%, ET 29 ± 12%; main effect P < 0.05). No training × group interactions were observed for any variables. In conclusion, SIT and ET both increase net IMTG breakdown during exercise and increase in PLIN2 and PLIN5 protein expression. The data are consistent with the hypothesis that increases in PLIN2 and PLIN5 are related to the mechanisms that promote increased IMTG utilization during exercise and improve insulin sensitivity following 6 weeks of SIT and ET.